"Why don't you become Jewish": identity politics in the encounter between Arab teachers and Jewish students in Israel. Issue 4 (4th July 2021) - Saada, Najwan; Gross, Zehavit
ABSTRACT: In this phenomenological and qualitative study, we explored the experiences of six Palestinian-Arab Israeli Arabic teachers working at K-12 Jewish schools in Israel. We examine the three models of intergroup contact according to Brewer and Miller's theorisation – category-based, differentiated, and personalised – and their potential in explaining the interaction between the teachers and their students. The results of this inquiry illuminate how the teachers challenge their students' limited understanding of Islamic and Arab culture. In addition, they clarify the limitations of differentiation-based contact. This means that developing a positive relationship at the interpersonal level may not necessarily lead to a positive change at the intergroup level. We also found that most students to continued holding negative associations at the intergroup level. The findings shed the light on the struggles and dilemmas of minority ethnic teachers teaching in mainstream schools in a conflicted society. Implications for teacher education programs are discussed as well.